2019
DOI: 10.1186/s12866-019-1626-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and assessment of lactic acid bacteria toward their selection as poultry probiotics

Abstract: BackgroundProbiotics are live microorganisms that, when administered in adequate amounts, confer a health benefit on the host, are now accepted as suitable alternatives to antibiotics in the control of animal infections and improving animal production. Lactic acid bacteria (LAB) with remarkable functional properties have been evaluated in different studies as possible probiotic candidates. The purpose of this study was to isolate, characterize and assess the potentials of LAB from poultry gastrointestinal trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
154
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(176 citation statements)
references
References 58 publications
22
154
0
Order By: Relevance
“…Human large intestine contains bile salt, whose concentration varies between 0.3%~0.5%. Generally, the pH of gastric juice depends on the time of feeding, diet and it may vary from 1.5 to 4.5 [43,44]. Growth and survival at low pH and in the presence of bovine bile are thought to be the most desirable characteristics for future probiotic strains.…”
Section: Discussionmentioning
confidence: 99%
“…Human large intestine contains bile salt, whose concentration varies between 0.3%~0.5%. Generally, the pH of gastric juice depends on the time of feeding, diet and it may vary from 1.5 to 4.5 [43,44]. Growth and survival at low pH and in the presence of bovine bile are thought to be the most desirable characteristics for future probiotic strains.…”
Section: Discussionmentioning
confidence: 99%
“…36 pathogenic bacteria in poultry, which in turn supports their use in improving the poultry performance and prevents transmission of poultry pathogens to humans. 37 We employed different strategies to confirm the inhibitory activity of the CFS. First, the classical well diffusion test was used as a screening tool.…”
Section: Discussionmentioning
confidence: 99%
“…L. acidophilus was reported the antibacterial activity against L. monocytogenes in cheese ( Ehsani et al., 2019 ). Enterococcus faecium isolated from poultry gastrointestinal tract could be used as a potential probiotic for preventing L. monocytogenes infection ( Reuben et al., 2019 ), and E. faecium selected from rabbit faeces showed an inhibitory activity against E. avium , L. innocua , and L. monocytogenes ( Simonová and Lauková, 2007 ). The anti-listerial activity of L. plantarum was via bacteriocin production and adhesion properties in vitro and in mice ( Van Zyl et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Possible action mechanisms of probiotics are involved in the modulation of intestinal barrier, defensin, inflammation, short-chain fatty acids, as well as cell interactions with hosts and pathogens ( Markowiak and Śliżewska, 2017 , Wang et al., 2019a , Wang et al., 2019b ). In recent studies, probiotic Lactobacillus plantarum and Lactobacillus acidophilus have been shown a significant anti-listerial activity ( Ehsani et al., 2019 , Reuben et al., 2019 , Van Zyl et al., 2019 , Zhao et al., 2020 ). However, whether probiotics influence the activities of virulence factors of pathogens including L. monocytogenes remains mostly unclear.…”
Section: Introductionmentioning
confidence: 99%